Older people’s beliefs on prevention and etiology of cancer in Poland. Implications for health promotion - Synowiec-Piłat, Małgorzata (Anthropological Review, 2015)
Introduction: Poland is among the countries with the highest mortality rates from cancer, and 75% of deaths from cancer occur after the age of 60. In the case of cancer, particular attention should be paid to beliefs people have in society. Aim of research: To learn about older people’s beliefs about the importance of preventive oncology care, individual’s responsibility for getting cancer, and the etiology of cancer. We analyzed the association between beliefs about cancer and the age of the respondents. Materials and Methods: The study was carried out in 2012 with a sample of 910 adult residents of Wrocław. An interview questionnaire was used. The article presents data on older adults (aged older than 56 years) (N = 188). Results: The vast majority of respondents recognize the need to engage in preventive oncology care. Only 5% of respondents hold fatalistic beliefs, 50% of older adults believe that “if someone is sick with cancer, it does not depend on them”. An association was confirmed that the oldest adults (65 years and older) are more likely to agree with the above statement, 34% disagree with the belief that “if someone is sick with cancer it depends largely on the lifestyle and the environment”. Discussion: In developing strategies for cancer prevention aimed at older adults, special attention should be paid to raising awareness about the impact of lifestyle on cancer incidence, increasing the sense of responsibility for their health, and reducing older adult’s “external locus of control” beliefs.